Decision Support System for Movie Recommendations Based on Multi User Preferences Using the Simple Additive Weighting Method - Allexandro Billy Sukarta; M. Mahaputra Hidayat; Rifki Fahrial Zainal (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
At this time advances in technology and information have experienced rapid progress, one of which is in the field ofentertainment, both audio and visual. And one of the entertainments is movies. With the increasing number of movies,there are several classifications of movie genres to assist users in finding and selecting movies to watch, but the genreclassification itself is still very general. Due to the above factors, especially in genre, subgenre, rating, movie durationwhich always develops over time according to a certain pattern and also audiences who have different moviepreferences, the researcher sees that there is a need for an application that can recommend movies with preferencesthat can be set according to the wishes of movie lovers. From the problems that arise, this research was built using theSimple Additive Weighting (SAW) method which aims to make it easier for users to determine which movie to choose.This system produces a web-based information system using several parameters, namely the main genre of a movie,subgenre, movie rating, movie duration, and year of making.